Syntheses of Novel 3,6-Dihydro and Klavuzon Derivatives - Kara, Murat; Çağır, Ali (Izmir Institute of Technology, 2015)
The styryl-lactones are a group of secondary metabolites which have unsaturated lactone moiety in their structures. One of the most important member of this group of compound is goniothalamin. Goniothalamin and its analogs having a common -unsaturated lactone moiety. Investigations on these species have been increased in the last decade because of their interesting biological activities. Present study aims the synthesis of novel 4’-alkyl substituted klavuzon and naphthalen-1-yl substituted 3,6-dihydro-2H-pyran-2-one derivatives. Syntheses were started with the preparation of ethyl 4-(bromomethyl)-1-naphthoate. Copper-catalyzed cross coupling reactions between ethyl 4-bromoethyl-1-naphthoate and Grignard reagents gave alkyl substituted esters. Next, alkylated ester derivatives were converted to alklylated-naphthaldehyde derivatives via reduction with LiAlH4 and then oxidation with PCC. Allylation reaction of corresponding aldehydes with allylmagnesium bromide gave homoallylic alcohols. Finally, homoallylic alcohols were reacted with acryloyl chloride in the presence of a base to produce acrylate esters, then ring closing metathesis by second generation Grubbs’ catalyst yielded the final klavuzon derivatives. Additionally, synthesis of new five -unsaturated lactone derivatives was also completed. Vinylation reaction of corresponding aldehydes with vinylmagnesium bromide gave the allylic alcohols. Coupling reactions of these alcohols with 3-butenoic acid in the presence of DCC/DMAP yielded the ester. Ring closing metathesis of the related ester was studied by using 2nd generation Grubbs’ catalyst.

Sitiril laktonlar, yapılarında doymamış yapıya sahip bir grup ikincil metabolitlerdir. Bu grubun en önemli üyelerinden birisi goniothalamindir. Goniothalamin ve onun türevleri doymamış yapıya sahiptir. Bu yapıya sahip moleküller üzerindeki araştırmalar bunların önemli miktarda biyolojik aktivite göstermelerinden dolayı son on yılda artmıştır. Bu çalışma 4’-alkil sübstitüentli klavuzon ve naftalin-1-il türevlendirilmiş 3,6-dihidro-2H-piran-2-on türevlerinin sentezlerini amaçlamaktadır. Sentezler etil 4-brommetil-1-naftoatın hazırlanmasıyla başlamıştır. Etil 4-bromometil-1-naftoat ve Grignard reaktiflerinin bakır katalizörlüğünde reaksiyonları sonucu alkil sübstitüentli esterler elde edilmiştir. Ardından alkillenmiş esterler LiAlH4 ile indirgenip, PCC ile yükseltgenerek alkillenmis naftaldehit türevleri elde edilmiştir. Alkillenmiş naftaldehitler allilmagnezyum bromür ile reaksiyona sokularak homoallilik alkoller elde edilmiştir. Son olarak homoallilik alkoller akriloyil klorür ile baz varlıgında reaksiyona sokulup akrilat esterler elde edilmiş ve 2. nesil Grubbs’ katalizörü varlığında halka kapanması reaksiyonu ile klavuzon türevleri elde edilmiştir. Ek olarak, yeni beş -doymamış lakton türevleri de sentezlenmiştir. Aldehitlerin vinilmagnezyum bromür ile reaksiyonları sonucu allilik alkoller elde edilmiştir. Alkoller vinil asetik asit ve DCC/DMAP katalizör varlığında estere dönüştürüldükten sonra 2. nesil Grubbs’ katalizörü ile halka kapanma reaksiyonları çalışılmıştır.
Yeni 3,6 Dihidro-2h-piran-2-on ve Klavuzon Türevlerinin Sentezleri
Thesis (Master)--İzmir Institute of Technology, Chemistry, 2015
Full text release delayed at author's request until 2018.08.06
Includes bibliographical references (leaves: 77-81)
Text in English; Abstract: Turkish and English
Keywords: Klavuzon; Lactones; Styryl lactones; Goniothalamin